RANCANG BANGUN PROTOTYPE SISTEM PENYORTIRAN BARANG MELALUI KODE WARNA (OURCODE) BERBASIS ARDUINO UNO - Ery Gunawan; Akhmad Burhan Maulana (Universitas Muhammadiyah Pekajangan Pekalongan, 2017)
The use of new and advanced technologies become the industry choice to improve production efficiency both in terms of quality, quantity and cost savings.Industrial automation process control system will not be separated from the use of electronic devices, such as the use of a wide variety of sensors and other critical components.Utilization component LDR (Light Dependent Resistor) is often only used as a light switch, but there are still many opportunities to be developed, for example as a component of a sensor that is able to identify the color, and could therefore conducted this research in order to utilize the components LDR is in the process of industrial automation, the process sorting items by using colors in the identification of goods, and to control the components used a microcontroller.Microcontroller is an electronic component that is capable of processing the data to be processed into work orders with the help of the program lines are inserted into it. Board Arduino UNO selected for use in this design because it is considered easy to be developed and studied.